The Kontribusi KURS, IHSG, dan JI Terhadap Pertumbuhan Ekonomi Indonesia 2013-2024 - Dwijayanto, Dyas Rizky; Iqbal, Muhammad; Rifan, Dinda Fali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research is motivated by the phenomenon of weakening economic growth in Indonesia, which often fails to align with financial sector dynamics due to exchange rate volatility. The primary problem addressed in this study is the extent to which exchange rate stability and capital market performance—both conventional and Sharia—serve as key determinants in driving national economic growth. This study aims to analyze the influence of the exchange rate, the conventional capital market (proxied by the Jakarta Composite Index or JKSE), and the Sharia capital market (jakarta islamic indeks JII ) on Indonesia’s ekonomic grwot ) for the 2013–2024 period. The research methodology employed is quantitative, using the Vector Error Correction Model (VECM) approach to capture both short-term and long-term relationships between variables. The results indicate that, partially, the exchange rate has a significant negative effect on Indonesia’s economic growth , while both conventional and Sharia capital markets show a significant positive influence. Simultaneously, these three independent variables contribute 89.4% to the variation in Indonesia’s economic grwoth, while the remaining 10.6% is explained by factors outside the model. These findings imply the importance of exchange rate stability policies to optimize the role of capital markets in accelerating the economy.